A CAPP system for axisymmetrical deep drawing parts. (12th June 2007) - Abbassi, Fethi; Ben Yahia, Nouredine; Zghal, Ali
A CAPP is an ideal tool to reduce design time and increase productivity. For that, in this paper, the authors proposed a theoretical study of the deep drawing parts and an assistance system developed under AutoCAD system. It is composed by three principal modules, the first relates to geometrical modelling in three dimensions, the second treats calculations of the stamping process parameters and the third module proposes the sequence design for the manufacture of axisymmetrical parts, the output of the CAD system are the stamping process parameters and the geometrical modelling of the tool. The development of this system is based on the experimental results and empirical knowledge of specialists in this field. This work starts with the proposal of several typical examples of processes, which are validated with industrialists and an original method developed to determinate all possible connections between elementary elements for moulding the shape of final parts.